Lateness, Asymmetricity, and Ecological Uncertainty in W.G. Sebaldâ€™s The Rings of Saturn - Spencer, Daniel (Journal of Ecohumanism, 2023)
This paper analyzes W.G. Sebaldâ€™s novel The Rings of Saturn as a literary exploration of ecology and post-historicity. By examining Sebaldâ€™s narrative through Timothy Mortonâ€™s revision of Hegelian art history as â€œAsymmetricity,â€ a prolonged period of post-human Romanticism, Sebaldâ€™s vision of history is positioned after the end of a sense of historical progress, a period of ruin and decline where nature begins to reclaim the landscape and history itself. This condition, I argue, is one instance in an ever-repeating cycle of historical and ecological â€œends,â€ whose foil is the concept of ecological melancholy. Ultimately this analysis is a case study in how literature of the Anthropocene so preoccupied with the notion of the â€œendâ€ encourages narrative estrangement from the world, an estrangement I seek to suture â€“ though not entirely heal â€“ through the recognition of a new historical teleology of engagement with the ecological melancholyâ€™s potential for rebuilding.